Impact of short-term protein supplementation on estrus, ovarian activity, and blood metabolites in Ossimi ewes synchronized with PGF2 α analogue (Cloprostenol) in subtropics. Issue 5 (28th May 2021) - Hussein, Hassan A; Mahmoud, Gamal B; Abdel-Raheem, Sherief M.; Mohamed, Ragab H.; Wehrend, Axel
ABSTRACT: The aim was to elucidate the effects of short-term, high protein diet on ovarian activity and metabolic status in synchronized Ossimi ewes. Fourteen Ossimi ewes divided into a high protein (HPG; n = 7) and a control group (CG; n = 7). Estrous synchronized using two doses of Prostaglandin F2α (PGF2α) that were administered 10 days apart. For the five days before the second dose of PGF2-α, a high protein diet consisting of 20% crude protein was fed to the HPG and the CG was provided a maintenance diet. The estrus period was significantly longer and the ovulation rate was significantly higher in the HPG as compared to the CG (P < 0.05). A significantly longer ovulation time and larger diameter ovulatory follicles were observed in the HPG (P < 0.05). A high protein diet had a significant effect on the number of recruited follicles and the diameter of the ovulatory follicle (P < 0.05). Significantly higher levels of estradiaol-17β, total protein, albumin, total cholesterol, blood urea, and glucose detected in the HPG as compared to CG ewes (P < 0.05). It is concluded that short-term, high protein flushing may improve estrus expression, ovarian activity, and metabolic status in PGF2α analog synchronized Ossimi ewes.